Regeneration and new urban interventions the Polis programme in Portugal - Fátima Loureiro de Matos (2006)
The theme of urban renewal and environmental quality in cities hasdrawn increasing attention over the last few years in Portugal. The RegionalDevelopment Plan for the 2000-2006 period has set the regeneration of urban areas andtheir environmental improvement as ones of its major aims, considered of strategicimportance for the country's development.In this paper we propose to analyse one of the programmes of urban regenerationthat was implemented in Portugal in 2000 (Resolution of the Ministers Council nº26/2000), whose major goal was the improvement of the quality of life in cities, fromurban and environmental operations, to increasing the attractiveness of cities and theircompetitiveness in the National Urban Network System - Programa de RequalificaçãoUrbana e Valorização Ambiental das Cidades (POLIS).